2008
DOI: 10.1057/dbm.2008.16
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national segments for a food product: Defining them and a strategy for finding them in the absence of ‘Mineable’ databases

Abstract: is president of Moskowitz Jacobs Inc., founded in 1981. He is an experimental psychologist in the fi eld of psychophysics (the study of perception and its relation to physical stimuli), and inventor of world-class market research technology. Moskowitz graduated from Harvard University and he has written / edited 16 books, published over 300 refereed and conference articles, lectures widely, serves on the editorial board of major journals, and mentors numerous students. Jacqueline H . Beckleyis Founder and Pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In other cases, a more powerful variation can be found that cuts across markets, which can be particularly useful for international marketing. 12 In a research project for a software company targeting industry-specifi c software plug-ins, it was found that industry variation was much less important than end-user attitude and behaviour. Differences between bankers, lawyers and other professionals were less important than differentiation cutting across all professional groups.…”
Section: Customer-led Market Differentiation : Consumers and Businessesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, a more powerful variation can be found that cuts across markets, which can be particularly useful for international marketing. 12 In a research project for a software company targeting industry-specifi c software plug-ins, it was found that industry variation was much less important than end-user attitude and behaviour. Differences between bankers, lawyers and other professionals were less important than differentiation cutting across all professional groups.…”
Section: Customer-led Market Differentiation : Consumers and Businessesmentioning
confidence: 99%
“…Insuffi cient involvement of top management from across the business functions; 18. Not fi nding simple and effective ways of tagging customers to segments; this typically leads to insights without the capability to act on them; Moskowitz et al indicate one of many approaches to overcome this problem, 12 while Tesco and Harley-Davidson indicate other approaches. 19.…”
Section: Barriers and Better Alternativesmentioning
confidence: 99%